STRATEGI UNTUK MENGATASI KESULITAN MENULIS DALAM TEKS RECOUNT UNTUK SISWA INKLUSI - husna, atikasari; Multazim, Akhmad (Universitas Nusantara PGRI Kediri, 2019)
The objective of this study is to find out the teachers’ strategies to solve the students’ difficulties in writing recount text. This study was conducted in the eighth grade of an inclusion class in Yogyakarta. The study belongs to a qualitative research. The participant of this study was three teachers of English. The study investigation was done by interviewing the three teachers of English at Junior High School. The data collecting technique were interview and recording. There were several steps to analyse the data: first, analysing the students’ difficulties, then interviewing the teachers and the last step is descriptive analysis. The result of the study shows that the teachers’ strategies to solve the difficulties are: (a) in content aspect, the teachers used picture series as the learning media and guided writing; (b) in organization aspect, the teachers used guided writing; (c) in grammar aspect, the teachers used random word, modelling of text and mini dictionary product; (d) in mechanic aspect, the teachers recommended to improve reading habit of students; (e) in generic structure of recount text aspect, the teachers used semi guided and supported by picture series as learning media.